Mass Transfer Behavior of Benzene in Hierarchically Structured ZSM-5 - Meng, Xiuhong; Lin, Chunhui; Zhang, Youhua; Qin, Huibo; Cao, Shui; Duan, Linhai (Frontiers in Chemistry, 2019)
A series of ZSM-5 zeolites with hierarchical porous structure were synthesized using NaOH solutions treatment method. The structural and acidity properties of hierarchical ZSM-5 zeolites as-synthesized were characterized by X-ray diffraction (XRD), N2 adsorption, scanning electron microscope (SEM), NH3-temperature programmed desorption (TPD), and pyridine Fourier transform infrared spectroscopy (Py-FTIR). The adsorption and diffusion performances of benzene in hierarchical ZSM-5 zeolites were studied by an intelligent gravimetric analyzer (IGA). It was found that the mass transfer (adsorption and diffusion) performance of benzene was significantly affected by synergetic effect of hierarchical structure, acid amount, acidity, adsorption sites of ZSM-5 zeolites. After suitable alkali treatment, the structure of ZSM-5 was retained and finely tailored. The hierarchical ZSM-5 was obtained with a uniform size of mesoporous and microporous structure. The acidity of hierarchical ZSM-5 zeolites was improved, which produced more adsorption sites and thus increased the adsorption performance of benzene in hierarchical ZSM-5. As a result, the connectivity in hierarchical ZSM-5 was improved with increasing of mesopores in hierarchical ZSM-5. Hierarchical ZSM-5 well contributed to the adsorption performance of benzene on active sites and improved the catalytic performance of hierarchical ZSM-5.